Modulation of cyclophosphamide-induced immunosuppression and intestinal flora in broiler by deep eutectic solvent extracted polysaccharides of Acanthopanax senticosus - Su, Jianqing; Xue, Jiaojiao; Wang, Xueyan; Zhang, Rui; Zhang, Xueping; Yang, Yaosen; Chu, Xiuling (Frontiers in Veterinary Science, 2024)
Introduction The aim of this experiment was to investigate the modulation effect of Acanthopanax senticosus polysaccharide (ASPS-PD) extracted with deep eutectic solvent on cyclophosphamide-induced immunosuppression in broilers and its modulation of the gut microbiota of broilers. Methods The 108 one-day-old broilers were divided into six groups, including the control group, the Cyclophosphamide (CY) model group, the ASPS-PD control group, the ASPA-PD high and low dose groups and the Astragalus polysaccharide group. Body weight, feed intake, feed conversion ratio, and immune organ index of broilers at 7, 14, and 21 days were determined; IL-2, IFN-γ, and lgG1 levels were determined by enzyme-linked immunosorbent assay (ELISA); Broiler caeca feces were analyzed by amplification and 16S rRNA sequencing. Results The results showed that ASPS-PD can restore growth performance, increase immune organ index and improve serum cytokine levels of IL-2 and IFN-γ and immunoglobulin lgG1 levels in CY-treated broilers. The analysis of cecum flora showed that ASPS-PD can promote the proliferation of beneficial bacteria and reduce the number of harmful bacteria, regulating intestinal flora. Discussion Therefore, ASPA-PD may be a potential novel immunomodulator to ameliorate CY-induced immunosuppression and intestinal flora dysregulation in broiler.